Idarucizumab in Dabigatran-Treated Patients with Acute Ischemic Stroke Receiving Thrombolytic Therapy - Ilga Kikule; Alise Baborikina; Iveta Haritoncenko; Guntis Karelis (Medicina, 2022)
Background and Objectives: Thrombolytic therapy with recombinant tissue-type plasminogen activator (rt-PA) is used to treat acute ischemic stroke. Dabigatran is a reversible thrombin inhibitor approved for stroke prevention in patients with nonvalvular atrial fibrillation. In such cases, thrombolytic therapy can be administered to certain patients after idarucizumab treatment. We evaluated the effectiveness of idarucizumab in dabigatran-treated patients receiving rt-PA. Materials and Methods: We included the data of nine idarucizumab-treated patients from the Riga East University Hospital Stroke Registry from 2018 to 2022 in our retrospective medical records analysis. We used the National Institutes of Health Stroke Scale (LV-NIHSS) score and modified Rankin scale (mRS) on admission and discharge to evaluate neurological deficit and functional outcomes. Results: We analyzed the data of nine patients (seven males and two females) with a mean age of 75.67 ± 8.59 years. The median door-to-needle time for all patients, including those who received idarucizumab before rt-PA, was 51 min (IQR = 43–133); the median LV-NIHSS score was 9 (IQR = 6.0–16.0) on admission and 4 (IQR = 2.5–4.0) at discharge; and the intrahospital mortality rate was 11.1% due to intracranial hemorrhage as a complication of rt-PA. Conclusions: Our study shows that idarucizumab as an antidote of dabigatran appears to be effective and safe in patients with acute ischemic stroke. Furthermore, the administration of idarucizumab slightly prolongs the door-to-needle time; however, the majority of cases showed clinical improvement after receiving therapy. Further randomized controlled trials should be performed to evaluate the safety and effectiveness of idarucizumab for acute ischemic stroke treatment.